Estimation of Leaf Photosynthetic Capacity From Leaf Chlorophyll Content and Leaf Age in a Subtropical Evergreen Coniferous Plantation. Issue 2 (20th February 2020) - Wang, Shaoqiang; Li, Yue; Ju, Weimin; Chen, Bin; Chen, Jinghua; Croft, Holly; Mickler, Robert A.; Yang, Fengting
Abstract: Photosynthetic rate is a key source of uncertainty in the modeling of the terrestrial carbon cycle. Recent studies have utilized leaf chlorophyll content (Chl) as a proxy for leaf photosynthetic capacity in croplands and deciduous forests, with little investigation into this relationship for other plant function types and for different leaf ages. In this study, we evaluated the relationship between the maximum rate of carboxylation (Vcmax25 ) and the maximum electron transport capacity (Jcmax25 ) at 25 °C with both leaf nitrogen and Chl from different leaf ages (current and previous year) in Masson's pine ( Pinus massoniana Lamb.) and slash pine ( Pinus elliottii Engelm.) species in a subtropical evergreen coniferous forest. Our results showed small changes in leaf nitrogen over the growing season. In contrast, Vcmax25, Jmax25, and Chl displayed larger seasonal variations. Vcmax25 was more related to leaf Chl than leaf nitrogen in both previous year's and current year's leaves, likely due to the variable partitioning of leaf nitrogen between and within photosynthetic and nonphotosynthetic fractions. Leaf Chl and month after budding (MAB) were the main predictors for Vcmax25 based on the random forest regression analysis. These findings highlighted the problem in using leaf nitrogen as a proxy for Vcmax25 where there is a dynamic nitrogen investment (i.e., with leaf ontogenesis, or between different species) and illustrated the value of using leaf Chl (as retrievable from remotely sensing) and MAB to constrain Vcmax25 in process‐based models to improve the simulation of photosynthetic rates in evergreen coniferous forests. Plain Language Summary: The parameter (Vcmax25 ) representing leaf photosynthetic capacity within models is usually assumed to be constant, which leads to a key source of uncertainty in the simulation of the terrestrial carbon cycle. To consider the time‐varying photosynthetic capacity parameter, recent studies have utilized leaf chlorophyll content (Chl), instead of leaf nitrogen, as a proxy for the parameter in croplands and deciduous forests to reduce this uncertainty. However, there is little investigation into this relationship in evergreen coniferous forests. In this study, we evaluated the relationship between the photosynthetic capacity parameter and both leaf nitrogen and chlorophyll of different leaf ages (current and previous year) in a subtropical evergreen coniferous forest. Vcmax25 was more related to leaf Chl than leaf nitrogen, likely due to the dynamic partitioning of leaf nitrogen between and within photosynthetic and nonphotosynthetic fractions. Leaf Chl and month after budding (MAB) were the main predictors for Vcmax25 . These findings highlighted the problem in using leaf nitrogen as a proxy for Vcmax25 where there is a dynamic nitrogen investment among photosynthetic components and illustrated the value of using leaf chlorophyll and MAB to constrain Vcmax25 in models to improve the simulation of photosynthetic rates in evergreen coniferous forests. Key Points: There were weak correlations between leaf nitrogen and the maximum carboxylation rate of two leaf ages The fractions of leaf nitrogen partitioning among photosynthetic components were dynamic The combination of leaf chlorophyll and month after budding was a better proxy for the maximum carboxylation rate